Credo - Starnino, Carmine (Hugh MacLennan poetry series., 2000)
The elegance, verbal felicitousness, and subtle crafting that were the signature qualities of Carmine Starnino's debut, The New World, are once again on display in his second book, Credo. Whether the subject is a passport, a clothesline, an antique goblet, prayer, or archaic English words, Starnino exercises an arresting mixture of wit and wordplay that rejoices in its own resources, its own cadence and diction. Credo places Starnino in the forefront of a new generation of Canadian poets.